21st century Chinese arms modernization and statecraft in Southeast Asia - De Castro, Renato C. (Animo Repository, 2007)
Using the concept of strategic culture, this article examines China's current arms modernization programs vis-à-vis its foreign policy of peaceful emergence. The article observes that these military modernization programs complement Beijing's overall policy of affecting a peaceful emergence, since both are pursued to restrain and counterbalance American power and influence in Southeast Asia. It likewise notes that the arms modernization programs are limited and are primarily aimed against Taiwan and any third country that might intervene in case of a cross-Strait crisis. In conclusion, the article asserts that the United States should not merely focus on China's hard power but should also match its soft power diplomacy in Southeast Asia, which might be more effective in undermining American strategic preponderance and initiative in the region.